Endoscopic retrograde cholangiopancreatography in giant lithiasis of the bile tract: case report and literature review - Corona, Alexandro; Zepeda, José M.; Bustos, Fabiola; Contreras, Javier; Osuna, Felix (International Surgery Journal, 2021)
In Mexico, the prevalence of biliary disease is 8.5% in men and 20.5% in women. Choledocholithiasis is a frequent clinical entity, predominantly in females and with well-defined risk factors. Obstruction of the bile duct due to stones is called giant choledocholithiasis when the largest diameter of the stone is greater than 15 mm. Endoscopic treatment fails in up to 88% of cases of giant choledocholithiasis. The authors presented the case of a patient suffering from giant choledocholithiasis, of 9 years of evolution, with an endoprosthesis, successfully treated by ERCP (endoscopic retrograde cholangiopancreatography). The selection of patients who will undergo this type of procedure must be careful, multidisciplinary management is essential to maintain the optimal conditions possible for each case, since the risks are usually high, it is a fact that the diameter of the distal bile duct it is the most important predictive factor when selecting the diameter of the balloon to use, since excessive dilation increases the risk of perforation.